Somatic Processing in Trauma Recovery: The Efficacy of Brainspotting for a Deaf Adolescent with PTSD (Single Case Experimental A–B Design) - Yasir; Ika Wulansari (Universitas Islam Negeri Raden Intan Lampung, 2026)
Deaf children face heightened vulnerability to sexual violence yet remain underserved by evidence-based trauma therapies. This single-case experimental A-B design specifically assessed Brainspotting, a somatic-focused therapy, for a 17-year-old deaf child diagnosed with PTSD. Baseline assessment used the Child PTSD Symptom Scale. Intervention comprised three 60–90-minute sessions involving somatic orientation, brainspot identification, eye-focused trauma processing, and grounding. Results indicated PTSD severity reduced from severe to mild, alongside improved emotional regulation, decreased physical tension, and enhanced social interaction. These preliminary exploratory findings suggest clinical feasibility, emphasizing somatic processing in inclusive recovery. However, further rigorous research with larger, diverse samples remains essential. Keywords : Brainspotting, PTSD, Anak Tunarungu, Pemrosesan Somatik, Single-Case Experimental A-B Design